Perancangan Sistem Informasi Administrasi pada Perusahaan Jasa Penyaluran Tenaga Kerja ke Luar Negeri: Studi Kasus pada PT XYZ - Oktavia, Tanty (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Running the business process of labor supply is not easy since it involves several parties, and n supported by elements of the documents obtained from internal and external parties. PT XYZ as a company dealing with labor supply service to foreign countries has not had any competent information systems in supporting its business processes. Therefore, this research is expected to produce a draft of information system and database applications that can support the administrative activities of labor supply of the company. The research used both analysis and design methods. Analytical method includes survey of the current system done by observation, interviews, identification of the information needs of the survey results and identification of system requirements. The design method consists of designing a model system using UML notation, designing databases and user interfaces for supporting applications. The information system applications resulted in this research can be a competitive advantage in marketing their employment services and improve business processes of PT XYZ.